Cerebral perfusion and gray matter volume alterations associated with cognitive impairment in metabolic syndrome with cerebral small vessel disease - Liu, Han; Zheng, Wenhui; Geng, Jie; Zhou, Xia; Xia, Yu; Liu, Yan; Zhang, Gang; Zhu, Xiaoqun; Lv, Daping; Sun, Zhongwu (Frontiers in Aging Neuroscience, 2025)
ObjectiveMetabolic syndrome (MetS) combined with cerebral small vessel disease (CSVD) is associated with cognitive dysfunction. However, the underlying mechanisms remain poorly understood. This study investigated the roles of brain perfusion and gray matter volume (GMV) in cognitive dysfunction in patients with MetS combined with CSVD (MetS-CSVD).MethodsThis study enrolled 180 MetS patients and 86 healthy controls (HCs). Patients with MetS were categorized into MetS without CSVD (MetS-NCSVD) (n = 58) and MetS with CSVD (MetS-CSVD) (n = 122) groups. All participants underwent laboratory tests, neuropsychological assessments, 3D pseudo-continuous arterial spin labeling (3D-PCASL), and magnetic resonance imaging scans with voxel-based morphometry (VBM). Cerebral blood flow (CBF), GMV, and clinical scales were analyzed for correlations in regions of interest (ROIs). The relationships among cognitive performance, CBF, and GMV were evaluated using partial correlation analysis and multivariable linear regression analysis (MLRA). Mediation analysis was performed to investigate the roles of CBF and GMV in the association between CSVD scores and cognitive performance.ResultsCompared to the MetS-NCSVD and HC groups, the MetS-CSVD group displayed significantly reduced perfusion and GMV in the frontal and temporal lobes. Partial correlation analysis revealed that CBF and GMV in the frontotemporal lobe were strongly associated with overall cognitive function, executive function, and language function in the MetS-CSVD group. MLRA identified the CSVD score as the sole independent factor negatively associated with cognitive performance. Mediation analysis revealed that CBF and GMV in the frontal lobes mediated the relationship between the CSVD score and overall cognitive and executive function.ConclusionCBF and GMV were strongly associated with cognitive performance. CSVD, rather than individual components of MetS, mediated cognitive impairment in patients with MetS-CSVD. CSVD likely contributes indirectly to cognitive impairment through its effects on CBF and GMV in these patients.